2017
DOI: 10.1080/21665095.2017.1355738
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of economic efficiency among small-scale beekeepers in Tabora and Katavi regions, Tanzania: a stochastic profit frontier approach

Abstract: This study applied the stochastic profit frontier model to estimate the economic efficiency of smallscale beekeepers in the Tabora and Katavi regions of Tanzania. The results show that the profit of small-scale beekeepers is determined by changes in the cost of labor and materials such as wire and color paint for beehives. Reducing the cost of these can significantly increase profits in beekeeping production. Small-scale beekeepers were found to be economically efficient, with a mean efficiency of 92%. This im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Literature shows that the adoption of improved beehives technologies has a positive and significant impact on honey production [7,22,23]. This is an incentive for farmers to adopt or continue with the technology because the return to their efforts on investment is realized, that is, increased productivity [22].…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows that the adoption of improved beehives technologies has a positive and significant impact on honey production [7,22,23]. This is an incentive for farmers to adopt or continue with the technology because the return to their efforts on investment is realized, that is, increased productivity [22].…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with that of Amulen et al [36] who reported that beekeepers tended to adopt beekeeping following contact with non-government organizations and access to training. According to the findings of Kuboja et al [16], extension contact was the main factor that had a significant influence on the economic efficiency of small-scale beekeepers in Tanzania. In addition, frequency of extension contact significantly determines market outlet choice decision of honey producers [15].…”
Section: Econometric Analysis the First Step Heckman Regression Modelmentioning
confidence: 98%
“…The profit of small-scale beekeepers is determined by changes in the cost of labor and materials, such as wire and color paint for beehives. In addition, contacts and follow-up by beekeeping extension officers and access to beekeeping training on improved management practices were the main factors that had a significance influence on the economic efficiency of small-scale beekeepers in Tanzania [16]. A study conducted on the determinants of honey producer market outlet choice in Chena District, Southern Ethiopia by employing a multivariate probit regression model revealed that the quantity of honey sold, frequency of extension contact, beekeeping experience, distance to the nearest market, market information about each outlet, cooperative membership, and trust in buyers determine market outlet choice decision of honey producers [15].…”
Section: Empirical Literaturesmentioning
confidence: 99%
See 2 more Smart Citations